Ellipsometric study of ion implanted copper surface and its room temperature oxidation - Poperenko, L.V.; Lohner, T.; Stashchuk, V.S.; Khanh, N.Q.; Vinnichenko, M.V.; Yurgelevych, I.V.; Essam Ramadan Shaaban; Nosach, D.V. (Functional Materials, 2005)
The room temperature oxidation of ion-implanted copper surface has been studied ex situ and in situ using ellipsometry. The ellipsometric parameters T and Д were measured at light incidence angle 75° for different wavelength values in the range of 280 to 760 nm using averaging both over two azimuthal zones and single one. The oxide layer was removed from the copper surface during the aluminum ion implantation an then the growth of the newly formed oxide film on the ion implanted surface was studied by ellipsometry. Basing on the spectroellipsometric data, the oxide film thickness has been calculated for two types of copper oxides.